Dysregulation of Cell Signaling by SARS-CoV-2. Issue 3 (March 2021) - Suryawanshi, Rahul K.; Koganti, Raghuram; Agelidis, Alex; Patil, Chandrashekhar D.; Shukla, Deepak
Abstract : Pathogens usurp host pathways to generate a permissive environment for their propagation. The current spread of severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) infection presents the urgent need to understand the complex pathogen–host interplay for effective control of the virus. SARS-CoV-2 reorganizes the host cytoskeleton for efficient cell entry and controls host transcriptional processes to support viral protein translation. The virus also dysregulates innate cellular defenses using various structural and nonstructural proteins. This results in substantial but delayed hyperinflammation alongside a weakened interferon (IFN) response. We provide an overview of SARS-CoV-2 and its uniquely aggressive life cycle and discuss the interactions of various viral proteins with host signaling pathways. We also address the functional changes in SARS-CoV-2 proteins, relative to SARS-CoV. Our comprehensive assessment of host signaling in SARS-CoV-2 pathogenesis provides some complex yet important strategic clues for the development of novel therapeutics against this rapidly emerging worldwide crisis. Highlights: Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) proteins modulate host signaling to generate a permissive environment. SARS-CoV-2 proteins upregulate or downregulate ~100 human kinases involved in cellular physiology, metabolism, and immune activation. Targeting specific proviral cellular signaling could make the host microenvironment resistant to virus replication. Most of the nonstructural proteins of SARS-CoV-2 participate in dysregulating the immune response. Pertaining to the differences in sequence homology, NSP2 may be important in serodiagnosis.